Still's disease and myocarditis associated with recent mumps infection. Issue 755 (September 1988) - Ward, S. C.; Wiselka, M. J.; Nicholson, K. G.
Abstract : We describe a 16 year old patient who developed Still's disease with evidence of myocarditis. A rise in the mumps 'V' antigen indicated that the disease was associated with recent mumps infection.